2018
DOI: 10.1111/codi.14106
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of tumour regression grade in locally advanced rectal cancer: a systematic review and meta‐analysis

Abstract: In conclusion, the degree of TRG was of prognostic value in predicting long-term outcomes. The current challenge is the development of a high-validity tests to predict pCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 59 publications
1
48
0
Order By: Relevance
“…However, even though nCRT results in clinically significant tumor regression for most patients, a considerable portion of patients exhibit very poor or no response to treatment. The rate of non-responders in current literature is about 20-30% [14,32]. However, 53% of the patients in the current study had poor to no response to nCRT.…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…However, even though nCRT results in clinically significant tumor regression for most patients, a considerable portion of patients exhibit very poor or no response to treatment. The rate of non-responders in current literature is about 20-30% [14,32]. However, 53% of the patients in the current study had poor to no response to nCRT.…”
Section: Discussionmentioning
confidence: 48%
“…However, with routine clinical use of preoperative CRT, it was evident that tumor response to this treatment ranges from complete to absent response [8,15,26]. This led to the development of various scales designed to quantify the level of response to neoadjuvant therapy [14]. Many studies have shown that response to nCRT correlates with prognosis and specifically DFS [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations